(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2026)
Hypertension is a condition characterized by elevated systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg. Non-pharmacological management of hypertension can be achieved through the consumption of high-fiber (>6 g/100 g), antioxidant-rich, and potassium-rich (470 mg) snacks. One such option is snack bars made from purple sweet potato flour and plantain flour, serving as an alternative snack for hypertension patients. This study aims to evaluate the organoleptic and chemical quality (antioxidant activity, potassium, and dietary fiber) of snack bars made from purple sweet potato flour and plantain flour as an alternative snack for hypertension patients. This research employed an experimental method with a completely randomized design (CRD) involving 3 treatments and 2 replications. Variations in treatment were based on different proportions of purple sweet potato flour and plantain flour used, while the amount of wheat flour was kept constant at 25 g for each treatment. Organoleptic assessment was conducted at the Food Technology Science Laboratory, Department of Nutrition, Medan Health Polytechnic, Lubuk Pakam, by 60 semi-trained panelists, who were students from the Department of Nutrition, Medan Health Polytechnic, who had passed the Food Technology Science course. Chemical quality tests were performed at the Nutrition Laboratory, Faculty of Public Health, Airlangga University, Surabaya. Data were analyzed using one-way ANOVA, and if significant differences were found, a Duncan’s test was followed. The results showed that snack bars with the addition of 70 g purple sweet potato flour, 30 g plantain flour, and 25 g wheat flour achieved an average score of 4.34 (highly liked) across all organoleptic aspects, with an antioxidant activity of 231.806 ppm, potassium content of 0.330 mg, and total dietary fiber of 6.097%.